2023
DOI: 10.1177/15353702231160326
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of FAM111B inhibits tumor growth and promotes apoptosis by decreasing AKT activity in ovarian cancer

Abstract: Ovarian cancer is the most lethal gynecological tumor in women worldwide. FAM111B (family with sequence similarity 111 member B) is an oncoprotein associated with multiple cancers, but its biological functions in ovarian cancer remain elusive. In this study, FAM111B was overexpressed in ovarian cancer tissues and cell lines. Functional studies in vitro revealed that silencing of FAM111B inhibited ovarian cancer cell proliferation, invasion, and migration, as well as increased cell apoptosis. Furthermore, FAM11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Furthermore, the direct or indirect activation of FAM111B by p53 has also been reported [ 22 ]. Moreover, it has been previously shown that the knockout or silencing of FAM111B affects the expression of p53 and p53-related proteins, such as p16, BAG3, BCL-2, CCNB1 [ 22 , 23 , 24 ], AKT and caspase-1 [ 23 ]. Therefore, in addition to FAM111B’s role in DNA repair, its proposed cellular function can be extended to cell cycle regulation.…”
Section: The Biological Role Of Fam111a and Fam111b In Cellular Proce...mentioning
confidence: 99%
“…Furthermore, the direct or indirect activation of FAM111B by p53 has also been reported [ 22 ]. Moreover, it has been previously shown that the knockout or silencing of FAM111B affects the expression of p53 and p53-related proteins, such as p16, BAG3, BCL-2, CCNB1 [ 22 , 23 , 24 ], AKT and caspase-1 [ 23 ]. Therefore, in addition to FAM111B’s role in DNA repair, its proposed cellular function can be extended to cell cycle regulation.…”
Section: The Biological Role Of Fam111a and Fam111b In Cellular Proce...mentioning
confidence: 99%